Employing Genome-Wide SNP Discovery to Characterize the Genetic Diversity in Cinnamomum camphora Using Genotyping by Sequencing - Xue Gong (MDPI AG, 2021)
Cinnamomum camphora (L.) J.Presl is a representative tree species of evergreen broad-leafed forests in East Asia and has exceptionally high economic, ornamental, and ecological value. However, the excessive exploitation and utilization of C. camphora trees have resulted in the shrinking of wild population sizes and rare germplasm resources. In this study, we characterized 171 C. camphora trees from 39 natural populations distributed throughout the whole of China and one Japanese population. We investigated genetic diversity and population structure using genome-wide single-nucleotide polymorphism (SNP) identified by genotyping by sequencing (GBS) technology. The results showed the genetic diversity of the C. camphora populations from western China > central China > eastern China. Moreover, the Japanese population showed the highest diversity among all populations. The molecular variance analysis showed 92.03% of the genetic variation within populations. The average pairwise FST was 0.099, and gene flow Nm was 2.718, suggesting a low genetic differentiation among populations. Based on the genetic clustering analysis, the 40 C. camphora populations clustered into three major groups: Western China, Central China, and Eastern China + Japan. Eastern China’s population had the closest genetic relationship with the Japanese population, suggesting possible gene exchange between the two adjacent areas. This study furthers our understanding of the genetic diversity and genetic structure of C. camphora in East Asia and provides genetic tools for developing strategies of C. camphora germplasm utilization.